(untitled) (Libellarium: journal for research in the field of information and related sciences, 2011)
The aim of the paper is to present the monograph publications on Croats in Vojvodina from 1990 to 2008. The paper presents a list of 137 monographs published in the above period that are thematically related to the social and cultural life of Croats in Vojvodina. These works are of heterogenic nature by a series of features - ranging from their volume through the complexity and scope of the theme to their scientific relevance; nevertheless, what brings them all together is the same topic. The list of publications on Vojvodina Croats is published in a sequence that follows the classification in accordance with the Universal Decimal Classification and the alphabetic list of authors. Anonymous publications and publications with multiple authors are listed at the beginning. In addition, the paper contains a brief analysis of the place of publishing and the place of the author’s activity, the language of publication and the field of science and the topics they cover. The contribution of the paper lies in the compilation of a time-defined regional bibliography that has presented for the first time all the known monographs on Vojvodina Croats in the mentioned period.